2016
DOI: 10.1108/mip-06-2014-0107
|View full text |Cite
|
Sign up to set email alerts
|

Consumers ' beliefs about firm’s CSR initiatives and their purchase behaviour

Abstract: Purpose – The purpose of this paper is to investigate the relationships among corporate social responsibility (CSR) beliefs, support intentions and purchase behaviour of consumers. Although there is a rich stream of research reporting the relationship between CSR beliefs and support intentions, there is scant reporting on the mediating role of support intentions between CSR beliefs and purchase behaviour of consumers, hence presenting an opportunity to contribute to the marketing knowledge-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 53 publications
5
67
2
Order By: Relevance
“…Therefore, testing the significance of the beta coefficient, the test results show the p-value of 0.00 <0.05 (5% alpha), the null hypothesis is rejected and it was concluded statistical confidence level of 95% a positive influence of customer purchase behavior on customer loyalty. The previous study conducted by Abdeen, Rajah, & Gaur (2016) reveals that there is a positive influence between philanthropic beliefs with purchase behavior. The results of these studies are supported by the research of Bhattacharya & Sen (2003) regarding the concept of consumer-company identification theory.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Therefore, testing the significance of the beta coefficient, the test results show the p-value of 0.00 <0.05 (5% alpha), the null hypothesis is rejected and it was concluded statistical confidence level of 95% a positive influence of customer purchase behavior on customer loyalty. The previous study conducted by Abdeen, Rajah, & Gaur (2016) reveals that there is a positive influence between philanthropic beliefs with purchase behavior. The results of these studies are supported by the research of Bhattacharya & Sen (2003) regarding the concept of consumer-company identification theory.…”
Section: Resultsmentioning
confidence: 91%
“…Arli, Rundle-Thiele, & Lasmono (2015), explains that the company's behavior reflects the characteristics of an idea that became the standard for the consumer to itself. While research Abdeen, Rajah, & Gaur (2016) stated that the ethical aspects of companies have a significant impact on consumers. These investigations showed that consumers can be persuaded to change purchasing behavior through effective presentation of information on relevant and 110 Jurnal Manajemen dan Pemasaran Jasa Vol.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are a whole lot of studies supporting the impact of CSR on consumer behavior either directly or indirectly(Abdeen, Rajah, & Gaur, 2016; Amoroso & Roman, 2015; Lee & Lee, 2015; Lee & Shin, 2010; Sen & Bhattacharya, 2001; Wong pitch, Minakan, Powpaka, & Laohavichien, 2015). There are a whole lot of studies supporting the impact of CSR on consumer behavior either directly or indirectly(Abdeen, Rajah, & Gaur, 2016; Amoroso & Roman, 2015; Lee & Lee, 2015; Lee & Shin, 2010; Sen & Bhattacharya, 2001; Wong pitch, Minakan, Powpaka, & Laohavichien, 2015).…”
mentioning
confidence: 99%